Detecting Hyperjacking in cloud based virtual environment - Beniel Dennyson W, Dr. S. Prabakaran (International Journal of Advanced Science and Technology, 2020)
Hypervisor vulnerabilities can favour the attacker to use the VM (virtual machine) for a longer period and pay less amount by resetting/manipulating the variables (i.e. which store CPU and memory etc. usage of VM, used by user, to charge him at the end) resulting in an attack called theft-of-service attack. This attack caused by stealing VM, can affect the cloud infrastructure financially as well as there will be no record of user’s activity during his stay on cloud which lead to a greater risk to success of cloud computing.